Development of the GEQUAL website to raise awareness of gender equality among high school students - Nunuk Rizqiani; Sigit Sanyata (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2026)
Gender-based violence in educational settings remains a persistent concern, while efforts to promote gender equality awareness among adolescents are still limited by the lack of engaging digital guidance services. This study aimed to develop a website-based guidance intervention to improve gender equality awareness among high school students. A research and development design was employed using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected from 64 students in two high schools in Gunungkidul Regency through interviews, questionnaires, and a gender equality awareness scale. The feasibility and practicality of the website were assessed through expert validation, counselor review, and student responses, while its effectiveness was tested using a pretest-posttest design. The results showed that the website achieved a very high level of feasibility and practicality. In the experimental group, students’ gender equality awareness increased significantly after the intervention, t(29) = -7.933, p < .001, with a moderate effect size (Cohen’s d = 0.65). In contrast, the control group showed no significant improvement. These findings indicate that a website-based guidance intervention can serve as an effective and innovative medium for enhancing gender equality awareness in school counseling services.